Assessment of factors that influence physician decision making regarding medication use in patients with dementia at the end of life. (9th July 2013) - Parsons, Carole; McCorry, Noleen; Murphy, Kevin; Byrne, Stephen; O'Sullivan, David; O'Mahony, Denis; Passmore, Peter; Patterson, Susan; Hughes, Carmel
<x xml:space="preserve">Abstract</x> Objective This study aimed to evaluate the extent to which patient‐related factors and physicians' country of practice (Northern Ireland [NI] and the Republic of Ireland [RoI]) influenced decision making regarding medication use in patients with end‐stage dementia. Methods The study utilised a factorial survey design comprising four vignettes to evaluate initiating/withholding or continuing/discontinuing specific medications in patients with dementia nearing death. Questionnaires and vignettes were mailed to all hospital physicians in geriatric medicine and to all general practitioners (GPs) in NI (November 2010) and RoI (December 2010), with a second copy provided 3 weeks after the first mailing. Logistic regression models were constructed to examine the impact of patient‐related factors and physicians' country of practice on decision making. Significance was set a priori at p ≤ 0.05. Free text responses to open questions were analysed qualitatively using content analysis. Results The response rate was 20.6% (N = 662) [21.1% (N = 245) for GPs and 52.1% (N = 38) for hospital physicians in NI, 18.3% (N = 348) for GPs and 36.0% (N = 31) for hospital physicians in RoI]. There was considerable variability in decision making about initiating/withholding antibiotics and continuing/discontinuing the acetylcholinesterase inhibitor and memantine hydrochloride, and less variability in decision making regarding statins and antipsychotics. Patient place of residence and physician's country of practice had the strongest and most consistent effects on decision making although effect sizes were small. Conclusions Further research is required into other factors that may impact upon physicians' prescribing decisions for these vulnerable patients and to clarify how the factors examined in this study influence prescribing decisions. Copyright © 2013 John Wiley & Sons, Ltd.